PRIMARY OPEN-ANGLE GLAUCOMA IN ONCOLOGIC PATIENTS - A. A. Ryabtseva; E. E. Grishina (Alʹmanah Kliničeskoj Mediciny, 2016)
Background: Glaucoma-induced visual impairment negatively influences quality of life of oncologic patients. Yet, tumor in itself and methods of its treatment may promote glaucoma progression. Aim: To study characteristics and course of primary open-angle glaucoma in oncologic patients. Materials and methods: We analyzed case reports of 19 oncologic patients after primary open-angle glaucoma-related sinus trabeculectomy (34 eyes) and laser cyclopexy (1 eye). Diagnosed malignancies included colorectal cancer in 5 patients, uterine body and cervical cancer in 4 patients, chronic lymphocytic leukemia in 1 patient, renal cell carcinoma in 1 patient, adrenal cancer in 1 patient, prostatic cancer in 1 patient, breast cancer in 1 patient, vulvar cancer in 1 patient, tongue root cancer in 1 patient. Antiglaucomatous surgery was accomplished during the first 5 years from the diagnosis of tumor in 14 patients. In 9 patients, chemotherapy or hormone therapy was continued by the time of surgery. Follow-up of the patients was undertaken in 4–12 months after the antiglaucomatous operation; it included routine ophthalmological examination and dry eye syndrome functional tests. Results: Duration of postoperative period was 4 months or more. All patients had uveitis postoperatively. During late postoperative period, choroidal detachment was diagnosed in 4 patients. Bleb scarring was found in 2 patients. All patients received hypotensive treatment postoperatively including selective and non-selective beta-adrenergic blockers. Conjunctival and corneal xerosis was observed in all patients. Conclusion: In oncologic patients undergoing antiglaucomatous surgery, long-term (4 months or more) postoperative anti-inflammatory therapy is needed along with monthly ophthalmological follow-up during the first year after the operation. In patients with ongoing cytostatic drug treatment, artificial tear should be administrated.